The psychological foundations of culture - Schaller, Mark, 1962-; Crandall, Christian S., 1959- (Lawrence Erlbaum, 2004)
How is it that cultures come into existence at all? How do cultures develop particular customs and characteristics rather than others? How do cultures persist and change over time? Most previous attempts to address these questions have been descriptive and historical. The purpose of this book is to provide answers that are explanatory, predictive, and relevant to the emergence and continuing evolution of cultures past, present, and future. Most other investigations into ""cultural psychology"" have focused on the impact that culture has on the psychology of the individual. The focus of this bo.